Nonlinear tail dependence between the housing and energy markets - David Stenvall; Axel Hedström; Naoyuki Yoshino; Mohammed Gazi Salah Uddin; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2020)
This paper examines the tail dependence between energy and housing markets in the United States by using cross-quantilogram approach. Our main finding shows a housing returns are dependent on the oil returns in a large part of the return distribution, and that the housing returns are more likely to be low after extremely high oil market returns. Furthermore, we find a heterogeneous response for the housing market in different regions with regard to all commodities. This appears in terms of the size of the dependence structures, but also for the sign of the dependence on the commodities. The findings in this study are robust to controls of economic state variables. Our contribution to the literature is showing the effect of energy returns on the housing market in the full part of the housing return distribution. Furthermore, we study the relationship between housing returns on more energy commodities other than crude oil. Last, we find regional differences in the relationship between different energy commodities and housing returns.
Keywords: C14; C46; R31; 330; housing market; oil; coal; natural gas; tail-dependence; cross-quantilogram